Case report: COVID-19-associated refractory thrombotic thrombocytopenic purpura complicated with Guillain-Barré syndrome - Zhou, Rui; Chen, Shenjian; Luo, Qinghua; Zhang, Xinyue; Li, Fang; Huang, Wei; Sheng, Zhiyong (Frontiers in Neurology, 2023)
Thrombotic thrombocytopenic purpura (TTP), a rare and lethal thrombotic microangiopathy, is an autoimmune disease that can be triggered by viral infections such as COVID-19. This condition is characterized by hemolytic microangiopathy, thrombocytopenia, and neurologic alterations, possibly accompanied by fever and renal damage. Moreover, more than 220 patients with Guillain-Barré syndrome (GBS) have been reported in association with the COVID-19 infection. In this report, we present a case of a patient who developed refractory TTP complicated by GBS following a SARS-CoV-2 infection. We aimed to highlight the importance of accurately diagnosing neurological complications associated with a COVID-19 infection and to demonstrate our strategies for treating a patient with COVID-19 infection-related refractory TTP complicated by GBS.